Application of Cydia pomonella expressed sequence tags: Identification and expression of three general odorant binding proteins in codling moth. (6th December 2012) - Garczynski, Stephen F.; Coates, Brad S.; Unruh, Thomas R.; Schaeffer, Scott; Jiwan, Derick; Koepke, Tyson; Dhingra, Amit
Abstract The codling moth, Cydia pomonella, is one of the most important pests of pome fruits in the world, yet the molecular genetics and the physiology of this insect remain poorly understood. A combined assembly of 8 341 expressed sequence tags was generated from Roche 454 GS‐FLX sequencing of eight tissue‐specific cDNA libraries. Putative chemosensory proteins (12) and odorant binding proteins (OBPs) (18) were annotated, which included three putative general OBP (GOBP), one more than typically reported for other Lepidoptera. To further characterize CpomGOBPs, we cloned cDNA copies of their transcripts and determined their expression patterns in various tissues. Cloning and sequencing of the 698 nt transcript for CpomGOBP1 resulted in the prediction of a 163 amino acid coding region, and subsequent RT‐PCR indicated that the transcripts were mainly expressed in antennae and mouthparts. The 1 289 nt (160 amino acid) CpomGOBP2 and the novel 702 nt (169 amino acid) CpomGOBP3 transcripts are mainly expressed in antennae, mouthparts, and female abdomen tips. These results indicate that next generation sequencing is useful for the identification of novel transcripts of interest, and that codling moth expresses a transcript encoding for a new member of the GOBP subfamily.